"I Felt like My Practice Was Catching up with My Beliefs:" A Longitudinal Cognitive Study of Seven Early Career Literacy Teachers and Their Praxis. (3rd July 2021) - Broemmel, Amy D.; Swaggerty, Elizabeth A.; Rigell, Amanda; Blanton, Betty
ABSTRACT: Using a qualitative approach, this article reports findings of a longitudinal study of seven successful elementary educators from the inception of their final preservice field experience through the first seven years of their independent teaching. The research centers the development of teachers' literacy-related instructional practices over the course of their early teaching careers, as well as the factors that influenced and impacted their instructional choices. Through repeated surveys and a culminating reflective interview, the researchers examined patterns of literacy beliefs and practices reported by these teachers over time, as well as the extent to which they internalized and used those beliefs and practices. The authors share what impacted teachers' perceptions and practice of reading instruction throughout the formative stages of their teaching careers and suggest implications for teacher preparation programs in attending to pre- and early-career teachers' praxis.